Echoes of Empire: The Politics of Repatriation and Decolonial Praxis in 21st-Century European Museums - Alex Putra Pratama; Christian Napitupulu; Aman Suparman; Omar Alieva (Enigma Institute, 2025)
The universalist claims of major European museums are built upon collections inextricably linked to the history of colonial violence and asymmetrical power. In the 21st century, a global movement demanding the repatriation of cultural heritage has challenged the very ethical and political foundations of these institutions. This study investigates the complex dynamics governing repatriation and the significant gap between museums' stated decolonial ambitions and their institutional practices, treating this dysfunction as a form of structural pathology. This study employed a mixed-methods approach grounded in a decolonial methodological awareness. The first phase consisted of a systematic thematic analysis of 188 policy documents from 25 major European museums (2019-2025), identifying the core logic of institutional responses to repatriation claims. The second phase developed a heuristic framework—a qualitative analytical model—to explore the logical outcomes of this institutional logic across three archetypal scenarios: a high-profile plunder case, a contested acquisition, and the return of ancestral remains. This model is presented not as a predictive tool, but as a framework for making the power structures and pathogenic mechanisms of holding institutions more legible. The documentary analysis revealed four key symptoms of a systemic pathology: a pervasive